1996
DOI: 10.1016/0300-9440(95)00589-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the behaviour of particulate polymeric coatings in a corrosive environment. Influence of the concentration of metal particles

Abstract: In this work pretreated steel specimens were coated by a spinning process with particulate polymeric composites consisting of an epoxy resin (DOW 33 1) and iron powder. Applied coatings were roughly 70 pm thick and the contained quantity of iron particles was varied (7.5, 15,30% wt./wt.). The effect of the presence of iron particles in the coatings as well as the influence of their concentration on the evaluation of the coatings' behaviour in a corrosive environment (3.5% NaCl) was studied. Electrochemical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The low impedance values obtained after three weeks of immersion might be insufficient for a corrosion protective biointerface. Therefore, to improve the corrosion protection ability the formation of large particle agglomerates must be avoided [45][46][47]. One possible route is to increase the concentration of PCL in the coating, keeping the same amount of HA nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The low impedance values obtained after three weeks of immersion might be insufficient for a corrosion protective biointerface. Therefore, to improve the corrosion protection ability the formation of large particle agglomerates must be avoided [45][46][47]. One possible route is to increase the concentration of PCL in the coating, keeping the same amount of HA nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly observed that the steel coated by epoxy with Al 40% nanoparticles showed significantly high resistance compared to steel coated by epoxy without Al nanoparticles during the wet/dry cycles. This could be explained based on the expression, R 0 ρ × l, where R is the resistance, ρ is the specific resistivity (Ω cm −1 ) of the coated steel and l is the thickness (centimeter) of the coatings [23]. The thickness of the epoxy coatings with and without Al nanoparticles were 40 μm, since the same draw-down rod were used.…”
Section: Resultsmentioning
confidence: 99%
“…When these results are compared to the EDS analysis, it is seen that higher percent of metal particles in epoxy coating gives lower R p values. Such a correlation is known from literature [18,19] and is ascribed to the fact that higher metal particle content results in higher porosity of the dry film.…”
Section: Electrochemical Impedance Plots Analysismentioning
confidence: 82%
“…3), where it is assumed that the one at the highest frequencies represents the epoxy coating pore resistance, R p , and the coating capacitance, C p , while the other two time constants are related to the corrosion processes inside and underneath the epoxy coating. Namely, metal particles dispersed in epoxy coating may react with penetrated electrolyte and create new corrosion products, a process which is assumed to be related to the time constant R c,1 CPE 1 [18,19]. Also, when electrolyte reaches the metal substrate, its corrosion occurs, which may be presented by the time constant R c,2 CPE 2 [5,6].…”
Section: Electrochemical Impedance Plots Analysismentioning
confidence: 99%